Rethinking the Penalty of Illicit Enrichment Crime in Ethiopia: Lessons from Comparative Analysis - Diriba Adugna Tulu (Faculty of Law, Hasanuddin University, 2020)
The crime of illicit enrichment has been widely accepted as a useful mechanism for curbing corruption, both international and regional anti-corruption instruments. This article's main objective is to comparatively analyze the rationality and appropriateness of the penalty provided for illicit enrichment crime in the Ethiopian Corruption Crimes Proclamation compared with Hong Kong and Rwanda's legal regimes to draw some best lessons and way forwards for the identified problems. The article found that the Ethiopia Corruption Crimes Proclamation fails to set a minimum penalty limit and entails severe punishment in terms of imprisonment and fine that can convey a meaningful message to potential offenders. Thus, the penalty provided for the crime of illicit enrichment is designed in a manner in which the person who commits such crime has the chance to be less punished. In effect, this provision is inconsistent with the purpose of criminal law and major sentencing principles, but it also degenerates public confidence in the justice system. Therefore, Ethiopia needs to take a lesson from Hong Kong and Rwanda's experiences in incorporating severe and setting minimum limit of penalty for the crime of illicit enrichment that can convey a meaningful message to potential offenders.